Converting Aspartase into a β‐Amino Acid Lyase by Cluster Screening. Issue 4 (1st April 2014) - Vogel, Andreas; Schmiedel, Ramona; Hofmann, Ute; Gruber, Karl; Zangger, Klaus
Abstract: Aspartase, despite being one of the most specific enzymes known, shows potential for application in β‐amino acid synthesis. The substrate binding pocket of AspB from Bacillus sp. YM55‐1 was reshaped by enzyme engineering to accommodate crotonic acid. The mutant enzyme BSASP‐C6 yielded enantiopure ( R )‐3‐aminobutyrate from crotonic acid and ammonia. To obtain this mutant, a high‐throughput screening in combination with a focused permutational library was decisive for the success in this project. We achieved this by simultaneous randomisation of four residues within the substrate binding pocket and cluster screening in mixed population. Screening of 300 000 clones was necessary to find the BSASP‐C6 mutant which has β‐amino acid lyase activity. This exemplifies the need for efficient search and screening strategies in creating novel enzyme activities. The BSAPS‐C6 enzyme developed here surpasses the natural substrate functionality of aspartase and thus represents the proof‐of‐concept of application of this novel synthetic route to a broader set of β‐amino acids. Abstract : β‐Amino acids with aspartase mutants: Aspartase, despite being one of the most specific enzymes known, shows potential for application in β‐amino acid synthesis. By applying a combination of focused library design and cluster screening, we created an aspartate mutant with β‐amino acid lyase activity and thus open up a new platform to synthesize this interesting and important compound class. BSASP‐C6= Mutant of AspB from Bacillus sp. YM55‐1.